Investment analysis of Inditex SA - Slavkovová, Karolína (2017)
This bachelors thesis provides Investment analysis of the apparel company Industria de Diseno Textil,Inditex SA. The main objective is to form an investment recommendation based on an assessment whether its stock is overvalued, undervalued or trading at its intrinsic value. To answer this question, I have focused on Fundamental analysis, which is traditionally split into the analysis of global, industrial and firm environment. In the last section,Firm analysis, I have used the valuation models to calculate the fair price of the company's stock. At the end of my thesis, these valuation results are compared to the current market price and presented in a form of a graph, accompanied by a final investment recommendation.